2022
DOI: 10.1186/s12883-022-02980-z
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the Charlson comorbidity index in aged patients with intracerebral hemorrhage

Abstract: Background Comorbidities are common in aged intracerebral hemorrhage patients. The purpose of this study was to assess whether the Charlson Comorbidity Index (CCI) was associated with in-hospital death and short-term functional outcome in elderly patients (age ≥ 70) with intracerebral hemorrhage (ICH). Methods This was a retrospective cohort of aged ICH patients (≥70 years old) admitted within 24 hours of ICH onset. The CCI was derived using hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…More importantly, in HICH patients, poor functional outcome was independently correlated with larger hematoma volume and lower GCS score. Additionally, in multiple studies, a larger hematoma volume and lower GCS score were associated with increased morbidity and mortality [ 20 , [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, in HICH patients, poor functional outcome was independently correlated with larger hematoma volume and lower GCS score. Additionally, in multiple studies, a larger hematoma volume and lower GCS score were associated with increased morbidity and mortality [ 20 , [23] , [24] , [25] ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zhang et al’s study on 248 ICH patients aged 70 years and above found that certain pulmonary diseases (such as chronic obstructive pulmonary disease, chronic bronchitis, and pulmonary fibrosis) and cerebrovascular diseases (such as previous IS and transient ischemic attack) were common comorbidities in ICH, significantly impacting patient prognosis and treatment strategies. The Charlson Comorbidity Index (CCI) is used to quantify the impact of these comorbidities and is associated with short-term prognosis and hospital mortality in patients [ 28 ].…”
Section: Characteristics Of Ich In Geriatric Patientsmentioning
confidence: 99%
“…The accumulation of these changes can result in thickening and stiffening of the walls of small cerebral arteries and constriction of their lumens, ultimately reducing vascular wall elasticity and increasing intraluminal pressure, leading to rupture and bleeding [30] (Figure 2). Index (CCI) is used to quantify the impact of these comorbidities and is associated with short-term prognosis and hospital mortality in patients [28].…”
Section: Hypertensionmentioning
confidence: 99%
“…The hematoma's characteristics, such as ICH volume and the presence of IVH, appear to reduce its effect. 16…”
Section: Distribution Of Samples By Age and Outcomesmentioning
confidence: 99%